Simulating the freezing-thawing processes based on MODIS data in the Three-River Souce Region, China - Ju, Qin; Zhang, Rongrong; Wang, Guoqing; Hao, Wenlong; Wang, Qin; Liu, Yanli; Wang, Wei (Frontiers in Environmental Science, 2022)
The processes of soil freezing-thawing lead to soil water and heat movement in cold regions, which significantly influences the hydrological and energy cycles in the soil-plant-atmosphere system. This study presents a soil water content coupled with heat transfer model based on physical processes of water and heat movement in frozen soil. The model was calibrated and validated using the measured data of soil temperature and frost and thaw depth at 19 stations in and around the Three-River Source Region of China. The results show that the frozen soil model could capture the processes of soil freezing-thawing processes well at this region. The relationship between model parameters and climate and vegetation factors was analyzed using the observation data and remote sensing data obtained from MODIS, and results showed that the parameter c which represents the soil properties has a good correlation with longitude and vegetation coverage. A multi-regression model was established to estimate the model parameters in regions without observation data and its determination coefficient R2 was 0.82. The mean relative error between calibration and inversion parameters of 19 stations is 6.29%. Thus, the proposed method can be applied to cold regions without observation data to obtain the parameters and simulated the soil freezing-thawing processes.